Development of Digital Pocketbook About Fungi in Mount Merbabu National Park as the Supplement of Teaching Material at Senior High School - Hafizhasando, Ramajid; Saptono, Sigit; Parmin, Parmin; Rahayuningsih, Margareta (Journal of Innovative Science Education)
The challenge of improving the 21st-century education quality in the industrial revolution 4.0 erais that graduates are expected to have theknowledge skills, abilities in the field of technology, information media, and learning innovation skills for life and career skills. This research was aimed to develop a digital fungi pocketbook in Mount Merbabu National Park to improve student learning outcomes. This research was a Research and Development (R&D) study, which used the Gall, Gall, and Borg model. The data analysis techniques used were descriptive data analysis related to the validity of responses from users, while the N-gain test was used to determine the product's effectiveness. The results showed (1) the digital pocketbook developed had very valid criteria regarding aspects of media, language, and material (2) students and teachers gave responses to the digital pocketbook used in learning with very valid response criteria (3) the value of learning outcomes students showed improvement with moderate N-Gain scores. Thus, the digital pocketbook that was developed can be used as an additional learning source in learning Natural Sciences (Biology) in the face of the 21st century and the industrial revolution 4.0.